An integrated approach to obtain xylo-oligosaccharides from sugarcane straw: From lab to pilot scale - Brenelli, Lívia B.; Figueiredo, Fernanda L.; Damasio, André; Franco, Telma T.; Rabelo, Sarita C. [UNESP] (Elsevier, 2020)
Sugarcane straw (SS) is a widely available agricultural processing feedstock with the potential to produce 2nd generation bioethanol and bioproducts, in addition to the more conventional use for heat and/or electrical power generation. In this study, we investigated the operational parameters to maximize the production of xylo-oligosaccharides (XOS) using mild deacetylation, followed by hydrothermal pretreatment. From the laboratory to the pilot-scale, the optimized two-stage pretreatment promoted 81.5% and 70.5% hemicellulose solubilization and led to XOS yields up to 9.8% and 9.1% (w/w of initial straw), respectively. Moreover, different fungal xylanases were also tested to hydrolyze XOS into xylobiose (X2) and xylotriose (X3). GH10 from Aspergillus nidulans performed better than GH11 xylanases and the ratio of the desired products (X2 + X3) increased to 72% due to minimal monomeric sugar formation. Furthermore, a cellulose-rich fraction was obtained, which can be used in other high value-added applications, such as for the production of cello-oligomers.
Keywords: Deacetylation; Hydrothermal pretreatment; Sugarcane straw; Xylanases; Xylo-oligosaccharides